Penerapan Model Index Card Match Untuk Meningkatkan Al-Maḥarah Al-Qiraah Siswa Kelas VII MTs Maarif Al-Ishlaḥ Bungkal - Robiatun Husnul Khotimah; Murdianto Murdianto; Syamsul Muqorrobin (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to explain the application of the index card match model to improve al-maḥaraḥ al-qiraah class VII students of MTs Maarif Al-Ishlaḥ, Bungkal. This type of research is a class action. Data collection by observation and tests. Data analysis with descriptive statistics. The results of the study showed that the use of an index card match-based active learning model was able to increase the maharah al-qiraah grade VII students of MTs Maarif Al-Ishlah Bungkal in the even semester of 2021/2022. The application of the index card match active learning model in the first cycle of maharah al-qiraah results for class VII students of MTs Maarif Al-Ishlah obtained an average score of 69.4. The increase in the average score occurred in cycle II, which was 85.2, this showed a significant increase.